Entering architectural practice - Tait, James (Architect) (Abingdon, Oxon ; New York : Routledge, 2021)
"Entering Architectural Practice is a practical and honest guide for architecture students, entering the world of architectural practice. There is often a disconnection between what you are taught in architecture school and the actual practice of architecture in the workplace. As both a practicing architect and architecture school tutor, the author has first-hand experience of this disconnection and so helps students bridge this divide between academia and practice. Focused on providing industry insight, dispelling myths, and above all providing a combination of reality and hope to students of architecture entering the workplace, the book is beautifully and richly illustrated providing a compelling visual story alongside the invaluable information it imparts. Serious but enjoyable, thoroughly researched but highly approachable, this book is simply essential reading for every individual about to embark on a career in practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Vocational guidance; ARCHITECTURE / General